2021
DOI: 10.1002/aelm.202000978
|View full text |Cite
|
Sign up to set email alerts
|

Solution‐Processed High‐Performance ZnO Nano‐FETs Fabricated with Direct‐Write Electron‐Beam‐Lithography‐Based Top‐Down Route

Abstract: Zinc oxide (ZnO) has been extensively investigated for use in large‐area electronics; in particular, the solution‐processing routes have shown increasing promise towards low‐cost fabrication. However, top‐down fabrication approaches with nanoscale resolution, towards aggressively scaled device platforms, are still underexplored. This study reports a novel approach of direct‐write electron‐beam lithography (DW‐EBL) of solution precursors as negative tone resists, followed by optimal precursor processing to fabr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 75 publications
(97 reference statements)
0
7
0
Order By: Relevance
“…124 Comparing zinc naphthenate and zinc neodecanoate as resists for fabricating ZnO nanowires and FETs, Tiwale et al demonstrated that both the precursors gave similar electronic properties. 125 Electron beam lithography of iron naphthenate and the post-heat treatment of its patterns gave Fe 2 O 3 , which was used as a catalyst to grow carbon nanotubes. 126 Likewise, nickel and copper naphthenates can also be patterned and heat-treated in air or a reducing atmosphere to give either their oxides or metals, respectively.…”
Section: Spin-coatable Metal Oxide Resistsmentioning
confidence: 99%
“…124 Comparing zinc naphthenate and zinc neodecanoate as resists for fabricating ZnO nanowires and FETs, Tiwale et al demonstrated that both the precursors gave similar electronic properties. 125 Electron beam lithography of iron naphthenate and the post-heat treatment of its patterns gave Fe 2 O 3 , which was used as a catalyst to grow carbon nanotubes. 126 Likewise, nickel and copper naphthenates can also be patterned and heat-treated in air or a reducing atmosphere to give either their oxides or metals, respectively.…”
Section: Spin-coatable Metal Oxide Resistsmentioning
confidence: 99%
“…c,d) Reproduced under the terms of the CC‐BY Creative Commons Attribution 4.0 International license (http://creativecommons.org/licenses/by/4.0/). [ 89 ] Copyright 2020, The Authors, published by Wiley‐VCH. e) Schematic illustration for NIL, and nanoimprint mold and imprinted mask pattern featuring a 10 nm‐wide nanogap.…”
Section: Fabrication Stratagems Of Micro/nanostructuresmentioning
confidence: 99%
“…Besides, thanks to the precise manipulation of EBL, micro/nano field‐effect transistors (FETs) were constructed through novel method of direct‐write EBL (DW‐EBL), as shown in Figure 3c,d. [ 89 ] It was worth mentioning that ZnO FETs with a wide range of width variations from micro to nanometer dimensions have been successfully fabricated. Particularly, the mobility and current density of the FETs could be increased by decreasing the width of patterns.…”
Section: Fabrication Stratagems Of Micro/nanostructuresmentioning
confidence: 99%
See 2 more Smart Citations